Salt stress in melon (Cucumis melo L.) is alleviated by seed treatment with melatonin, modifying physiological and biochemical parameters = El estrés salino en melón (Cucumis melo L.) es aliviado parcialmente con el tratamiento de semillas con melatonina, modificando parámetros fisiológicos y bioquímicos - Castañares, Jose Luis; Daurelio, Lucas Damián; Bouzo, Carlos Alberto (Facultad de Ciencias Agrarias, Universidad Nacional del Litoral, 2024)
Melatonin (N-acetyl-5-methoxytryptamine) is a molecule with a reported importance in increasing tolerance to several types of stress. The present study investigates the effect of melon (Cucumis melo L.) seed treatment with melatonin solutions (0, 10, 50 and 100 μM) at two durations (6 and 12 h) on germination and initial growth of melon plants in salt stress. Germination under salt stress (14 dS m-1 EC) suffered a decrease, which is reversed after seed treatment with melatonin and followed to 80% with 10 and 50 μM solutions. Then, considering plant growing in salt stress (8 dS m-1 EC), the best growth and physiological and biochemical responses (xylem water potential, leaf relative water content, total chlorophyll, root viability, proline, malondialdehyde content, peroxidase and catalase activity) were measured in plants derived from 50 μM seed treatment. No changes were observed at the anatomical level. Results suggest that melatonin can alleviate the effect of salt stress during seed germination and early plant growth. There is a dose-dependent response.